Retorika Masyarakat Terkait Undang-undang nomor 15 tahun 2003 jo Undang-undang nomor 5 Tahun 2018 Terhadap Penerapan Mala in se/Mala Per se Sebagai Kebijakan Integratif Tindak Pidana Khusus Terorisme di Indonesia - Fadhilatul Amaliya; Anindya Rahma Fathiya; Dewi Sekar Pembayun; Devina Angelica (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the application of mala in se and mala per se concepts in the counter-terrorism policy in Indonesia, based on Law Number 15 of 2003 in conjunction with Law Number 5 of 2018. Terrorism is categorized as an extraordinary crime that causes serious harm both nationally and internationally. This research employs a literature review and normative legal approach to analyze the application of criminal law norms within the context of human rights protection. The findings show that terrorism, as a mala in se offense, requires a comprehensive legal approach that prioritizes not only national security but also the protection of civil rights. The enforcement of anti-terrorism laws, if applied too broadly and harshly, may violate the principles of due process and substantive justice. Therefore, counter-terrorism efforts must be based on the pro justitia principle, supported by independent oversight and active civil society participation to prevent abuse of power and maintain the integrity of the legal system.